The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19127207
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Predictors of Coronavirus-Related PTSD among Young Adults from Poland, Germany, Slovenia, and Israel

Abstract: The aim of this study was to reveal longitudinal predictors of coronavirus-related PTSD and the moderating roles of country, sex, age, and student status among young adults from Poland, Germany, Slovenia, and Israel. We included the following predictors: perceived stress, exposure to COVID-19, perceived impact of COVID-19 on well-being in socioeconomic status (PNIC-SES) and social relationships (PNIC-SR), fear of COVID-19, fear of vaccination, and trust in institutions. We conducted the study online among a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 60 publications
5
11
0
Order By: Relevance
“…Apart from the coronavirus-related PTSD, all variables assumed in hypothesis H5 were confirmed in the study as significant predictors of life satisfaction, considering the multivariate linear regression model. The results of this study are consistent with previous studies that found numerous associations between these variables [ 2 , 3 , 5 , 6 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 47 , 49 , 50 , 51 , 52 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. For example, longitudinal research confirmed that in the three waves of the COVID-19 pandemic high anxiety risk was related negatively to life satisfaction and positively related to high levels of stress among Polish university students [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Apart from the coronavirus-related PTSD, all variables assumed in hypothesis H5 were confirmed in the study as significant predictors of life satisfaction, considering the multivariate linear regression model. The results of this study are consistent with previous studies that found numerous associations between these variables [ 2 , 3 , 5 , 6 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 47 , 49 , 50 , 51 , 52 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. For example, longitudinal research confirmed that in the three waves of the COVID-19 pandemic high anxiety risk was related negatively to life satisfaction and positively related to high levels of stress among Polish university students [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
“…We have found relatively high prevalence rates of people dissatisfied with their lives (SWLS scores ≤ 20) among Polish university students ( n = 745, 47%) and a significantly lower number in Ukrainian students ( n = 545, 33%). The prevalence of life dissatisfaction during the first pandemic wave was 37% in the Polish sample and 40% in the Ukrainian group of students as suggested in our previous study [ 47 ]. So, we can conclude that the frequency of dissatisfied students significantly increased from the first to the second wave of the pandemic in the Polish sample while it slightly decreased in the Ukrainian group.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations